SOSOK LAKI-LAKI DALAM IKLAN MS GLOW FOR MEN “SEMUA JUGA BISA” - Fillmore Galih Wibisana, Kuirinus; Hasfi, Nurul; Lukmantoro, Triyono (Interaksi Online, 2024)
Male facial care advertisement has the aim of offering products as a solution to men's facial problems through the talent presented as the image of the product. Current facial care advertisements feature a metrosexual figure, but researchers found a different figure through the MS Glow For Men "Semua Juga Bisa" advertisement arguing that all men are capable of looking good without having to follow beauty standards. This research aims to describe the representation of the male figure and understand why MS Glow For Men presents the figure in the product advertisement with the tagline "Semua Juga Bisa". This research was conducted using qualitative method with semiotic analysis of Roland Barthes model. Researchers use various theories to describe the male figure in advertisements, namely the theory of social construction of reality, superiority/disparagement theory, and incongruity theory. Representation is seen with a constructionist approach that interprets symbols and language based on cultural and social meanings. The research resulted in the finding that the representation of the male figure displayed in the MS Glow For Men "Semua Juga Bisa" advertisement is the figure of a worker (working-class men as target consumers), risk takers (men are willing to do anything to achieve their dreams), violent figure (men use violence to solve problems), leader, loyal, and responsible (assertive male, decision-maker, obedient, and responsible for him and the group), facialist (men are interested in body care), and narcissist (men have high self-confidence and success comes from appearance). The male figure in the MS Glow For Men “Semua Juga Bisa” advertisement is an illusion that is presented with humor, but contains content that degrades the lower middle economic group, finally this advertisement persuades target consumers to follow the beauty standard